Hematology and serum biochemistry parameters for rescued common palm civets (Paradoxurus hermaphroditus) in different age groups - Ahmad, Ali Anwar; Jayarajah, Praveena; Han, Gwen Wong Yee; Yin, Serena Jocelyn Oh Wai; Abdullah, Rasedee (Japanese Society of Veterinary Science, 2017)
Currently, there are no complete parameters established for serum biochemistry and hematology for the determination of health status of rescued common palm civets (Paradoxurus hermaphroditus). In this study, blood samples were obtained from 18 adults and 15 juvenile civets caught on Singapore Main Island. Significant age-related differences (P<0.05) were noted in the hemoglobin, erythrocyte count, packed cell volume (PCV), total serum protein and globulin concentration in the adult civets showing higher values compared with the juvenile civets. The mean corpuscular volume (MCV), the alkaline phosphatase (ALP) and the phosphorus concentrations were significantly higher (P<0.05) in juveniles compared with adult civets.